Pooling hawks and doves: Interim-efficient labor contracts for other-regarding agents - Thomas Daske (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Behavioral contract theory typically argues that agents who differ in their intrinsic motivations to collaborate or to compete would be screened by principals or self-sort in labor market equilibrium. This view contrasts with the empirical observation that workers' perceived support from coworkers is a key factor for labor turnover. The present study considers a principal-multiple agents model with independent efforts. Agents are privately informed about their more or less pronounced altruistic (spiteful) preferences. It is shown that the interim-efficient labor contract is a pooling contract that ex interim Pareto-dominates any allocation that could be achieved under complete information. Hence, all parties prefer the composition of social types to be random. The distributive effects of interim-efficient contracting are closely related to the hawk-dove game, with workers suffering from less altruistic coworkers. The results indicate that corporate culture has a random component associated with workers' intrinsic motivations to collaborate or to compete.
Keywords: D82; D86; M50; 330